PENGARUH SENAM NIFAS TERHADAP LOW BACK PAIN DAN INKONTINENSIA URIN PADA WANITA PASCA MELAHIRKAN NORMAL 8-16 MINGGU DI KOTA SUKABUMI - Ulfah Karim; Erika Lubis (Jurnal Abdimas Musi Charitas, 2018)
In late pregnancy, complaints such as low back pain, varicose veins, hemorrhoids and pelvic pain are present. One of the common discomforts is low back pain. Maternal age at delivery is associated with an increased risk of urinary incontinence. This research is quasi experimental with pre and post design. by observing the effect of postnatal exercises training on Low Back Pain complaints with the parameters of Oswestry Disability for Low Back Pain Dysfunction and urinary incontinesia with QUID parameters. Intervention is done Exercisess. Exercises duration between 30-50 minutes in one practice session, frequency 3 times a week for 10 weeks. It is known that the value of p = 0.00 <0.01 with depedent test t test then this shows the effect of postpartum exercises on urine incontinence in women after normal delivery 8-16 weeks in Sukabumi City. From 11,92 different meaning. In the analysis of low back pain before and after the intervention (table 5.3) obtained p value = 0.00 so p <0.05 this shows there is a significant change between before and after the postnatal exercises interventions in women postpartum normal.Dari Low Back Pain measurement results with using the Questionnaire Oswestry Disability Index obtained a mean score before the 12.63 ± 1.25 intervention and the mean score after the intervention of 0.56 ± 0.96. So the difference between Low Back Pain score before and after intervention 12.07 ± SD 0.29. After a statistical test with an average Wilcoxon Test of ODI in normal postpartum women 8-16 weeks obtained p value of 0.00 indicates a significant change with 16 people experienced a decrease in ODI score. Thus one way to prevent and reduce low back pain in postpartum women is by doing exercises. So patients who are trained in postpartum exercises have a lower low back pain incidence and when a low back pain complaint attack is lighter.